Rice Crop Manager - Odisha - CGIAR Research Program on Rice (2021)
In Odisha, around 175000 recommendations have been generated for the rice growers. Farmers are interviewed through an extension staff and given a printed copy of the recommendation for their specific plot, to be followed for the entire season. Different extension channels of the state have been engaged for the dissemination.